A daily-use ceramic and its preparation method and application
By using the synergistic effect of components such as porcelain stone, talc, diopside, zircon, magnesite and MOF materials in daily ceramics, combined with zinc oxide and sodium polyacrylate, the cost of existing antibacterial ceramic products is solved. and the problem of poor antibacterial effect significantly improves the mechanical and antibacterial properties of ceramics and achieves long-term antibacterial effects.
Patent Information
- Application Number
- CN202311334478.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-16
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-10-16
AI Technical Summary
The existing antibacterial ceramic products have high antibacterial agent costs and poor antibacterial effect, which cannot meet the actual needs of daily ceramics in reducing bacterial transmission and pollution.
The synergistic effect of components such as porcelain stone, talc, diopside, zircon, magnesite and MOF materials is adopted, and the MOF materials are prepared through hydrothermal reaction, combined with zinc oxide and sodium polyacrylate, and dry press molding and Preparation of ceramic products by hot press sintering process.
It significantly improves the mechanical properties and antibacterial properties of daily ceramics, achieves long-term antibacterial effects, and has good application prospects.
Smart Images

Figure BDA0004495257260000141
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of daily-use ceramics, and more specifically, relates to a daily-use ceramic and a preparation method and application thereof. Background Art
[0002] Ceramic products, whether they are building wall and floor tiles, sanitary ware, or daily-use ceramics such as plates and bowls, are closely related to people's lives. People will come into contact with a large number of ceramic products at home or in public places. However, these ceramics are generally humid, easy to be contaminated and breed bacteria, and cause disease transmission, which seriously endangers human health. With the general improvement of human material living standards and civilization, self-protection awareness is increasing. It is increasingly urgent to create a good ecological environment that reduces germs as much as possible. Therefore, the universal use of antibacterial building sanitary ceramics, reducing excrement pollution and cross-infection in public places are increasingly demanding, which provides a broad prospect for the development of antibacterial sanitary ceramics.
[0003] CN115925388B discloses a method for preparing long-lasting antibacterial daily-use ceramics, which is specifically implemented in the following steps: step 1. preparing photocatalytic nanorods; step 2. coaxial coating modification; step 3. blending and composite treatment; step 4. grouting molding; step 5. preparing long-lasting antibacterial ceramics. The long-lasting antibacterial ceramics prepared by the preparation method of the present invention solve the problems of high cost of antibacterial agents, poor antibacterial effect and sustainability in existing antibacterial ceramic products, and have good application prospects in the field of daily-use ceramics.
[0004] CN113149678B discloses a high-performance antibacterial daily-use ceramic and a preparation method thereof. The daily-use ceramic of the present invention has high toughness and excellent antibacterial performance. Nano-aluminum silicate short fibers are beneficial to increase the toughness of the ceramics, and the modified nano-TiO2 in the glaze greatly improves the antibacterial property of the ceramics. The present invention applies glaze to the surface of the biscuit and then sintering to obtain the high-performance antibacterial daily-use ceramic, wherein the sum of the mass percentages of the raw materials of the biscuit is 100%, and the ceramic is made according to the following raw materials in mass percentage: quartz 24-36%, wollastonite 16-24%, kaolin 12-18%, celestite 10-16%, fluorite 4-8%, black talc 6-14%, nano-aluminum silicate short fibers 3-6%; the mass percentage of the modified nano-TiO2 in the glaze accounts for 48%; the glaze is applied to the surface of the biscuit, and the thickness of the glaze on the surface of the biscuit is 0.4-0.8mm.
[0005] CN114195388A discloses an antibacterial and wear-resistant daily-use ceramic and its preparation method. The antibacterial and wear-resistant daily-use ceramic comprises a daily-use ceramic body and a glaze layer, and the glaze layer is made of the following raw materials in parts by weight: 35-45 parts of zircon sand; 15-20 parts of baddeleyite; 4-8 parts of magnesite; 2-6 parts of calcite; 1-3 parts of molybdenum powder; 2-4 parts of erbium oxide; 2-4 parts of neodymium oxide; 3-7 parts of zinc oxide; 3-7 parts of tungsten oxide; 2-4 parts of silver powder; 3-5 parts of sodium lignin sulfonate; 3-5 parts of sodium tripolyphosphate; 25-35 parts of water. The antibacterial and wear-resistant daily-use ceramic of the present invention has excellent wear resistance and antibacterial properties through the mutual coordination of components and the control of the preparation method.
[0006] In summary, adding antibacterial components to daily-use ceramics can improve the antibacterial properties of daily-use ceramics, but the antibacterial daily-use ceramics in the prior art cannot meet the needs of actual production. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the defects and deficiencies in the prior art, and provide a daily-use ceramic and its preparation method and application. In parts by weight, the daily-use ceramic includes the following raw materials: 40 to 60 parts of porcelain stone; 10 to 20 parts of talc; 15 to 25 parts of diopside; 6 to 10 parts of baddeleyite; 1 to 3 parts of magnesite; 4 to 8 parts of MOF material; 2 to 6 parts of zinc oxide, 4 to 8 parts of sodium polyacrylate; 30 to 40 parts of water; the preparation method of the MOF material includes the following steps: dissolving indium salt, copper salt, nickel salt and 2-methylimidazole in ethanol aqueous solution to obtain a mixed solution, then hydrothermally reacting at 120 to 160°C for 10 to 20 hours, filtering, washing, and drying at 80 to 120°C for 10 to 14 hours to obtain MOF material. The daily-use ceramic of the present invention can significantly improve the mechanical properties and antibacterial properties of daily-use ceramics by utilizing the synergistic effect between the components, and has good application prospects.
[0008] The purpose of the present invention is to provide a daily-use ceramic.
[0009] Another object of the present invention is to provide a method for preparing daily-use ceramics.
[0010] Another object of the present invention is to provide an application of daily-use ceramics.
[0011] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0012] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0013] 40-60 parts of porcelain stone; 10-20 parts of talc; 15-25 parts of diopside; 6-10 parts of baddeleyite; 1-3 parts of magnesite; 4-8 parts of MOF material; 2-6 parts of zinc oxide, 4-8 parts of sodium polyacrylate; 30-40 parts of water;
[0014] The preparation method of the MOF material comprises the following steps:
[0015] Indium salt, copper salt, nickel salt and 2-methylimidazole are dissolved in an ethanol aqueous solution to obtain a mixed solution, which is then hydrothermally reacted at 120-160° C. for 10-20 hours, filtered, washed, and dried at 80-120° C. for 10-14 hours to obtain a MOF material.
[0016] Preferably, the indium salt is at least one of indium nitrate, indium acetate, and indium chloride; the copper salt is at least one of copper nitrate, copper acetate, and copper chloride; and the nickel salt is at least one of nickel nitrate, nickel acetate, and nickel chloride.
[0017] Preferably, the molar ratio of the indium salt, the copper salt, the nickel salt and the 2-methylimidazole is: 0.02-0.04:0.01-0.03:1:3-5.
[0018] Preferably, the particle size of the porcelain stone is 80-160 μm; the particle size of the talc is 60-140 μm; and the particle size of the diopside is 70-110 μm.
[0019] Preferably, the particle size of the baddeleyite is 120-160 μm; the particle size of the magnesite is 20-60 μm; and the particle size of the zinc oxide is 40-80 nm.
[0020] Based on the above-mentioned method for preparing daily-use ceramics, the preparation method comprises the following steps:
[0021] (1) Put porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water in a ball mill for ball milling;
[0022] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 300-500 mesh sieve;
[0023] (3) calcining the sieved powder at 500-700° C. in a muffle furnace under a nitrogen atmosphere for 4-6 hours, and then calcining at 800-900° C. in an air atmosphere for 2-4 hours. After calcination, grinding to obtain a powder is performed, and then the obtained powder is uniformly mixed with sodium polyacrylate, and a green body is formed into a shape by dry pressing, and the dry pressing pressure is 40-80 MPa; then the green body is hot pressed and sintered, and then naturally cooled to room temperature to obtain the product.
[0024] Preferably, in step (1), the ball milling speed is 100 to 300 rpm, and the ball milling time is 20 to 40 hours.
[0025] Preferably, in step (2), the vacuum drying temperature is 60 to 80° C., and the drying time is 12 to 16 hours.
[0026] Preferably, the specific steps of the hot pressing sintering are: heating up to 500-700°C at a heating rate of 2-4°C / min, keeping warm for 3-5h, then heating up to 1250-1350°C at a heating rate of 8-12°C / min, sintering at a sintering pressure of 40-60MPa, and sintering for 1-3h.
[0027] Based on the above-mentioned application of daily-use ceramics in the antibacterial field.
[0028] The present invention has the following beneficial effects:
[0029] (1) By adding diopside, baddeleyite and magnesite, the mechanical properties of daily-use ceramics can be significantly improved through the mutual coordination of the above components;
[0030] (2) By adding MOF materials, utilizing the carbonization of MOF materials, and then heat treating them in an air atmosphere, the original doping of nitrogen and carbon was achieved, which improved the antibacterial properties of the active metal components. Moreover, there was a synergistic effect between the MOF materials and zinc oxide, which further improved the antibacterial properties of the materials.
[0031] (3) By utilizing the synergistic effect between components, the mechanical properties and antibacterial properties of daily-use ceramics can be significantly improved, which has good application prospects. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0033] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0034] Example 1
[0035] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0036] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 8 parts of baddeleyite; 2 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0037] The preparation method of the MOF material comprises the following steps:
[0038] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0039] The particle size of the porcelain stone is 120 μm;
[0040] The particle size of the talc is 100 μm;
[0041] The particle size of the diopside is 90 μm;
[0042] The particle size of the baddeleyite is 140 μm;
[0043] The particle size of the magnesite is 40 μm;
[0044] The particle size of the zinc oxide is 60 nm;
[0045] The preparation method of the daily-use ceramic comprises the following steps:
[0046] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0047] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0048] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0049] Example 2
[0050] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0051] 60 parts of porcelain stone; 10 parts of talc; 25 parts of diopside; 6 parts of baddeleyite; 3 parts of magnesite; 4 parts of MOF material; 6 parts of zinc oxide, 4 parts of sodium polyacrylate; 40 parts of water;
[0052] The preparation method of the MOF material comprises the following steps:
[0053] 0.04 mol of indium acetate, 0.01 mol of copper chloride, 1 mol of nickel nitrate and 5 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 160° C. for 10 h, filtered, washed, and dried at 120° C. for 10 h to obtain a MOF material.
[0054] The particle size of the porcelain stone is 160 μm;
[0055] The particle size of the talc is 60 μm;
[0056] The particle size of the diopside is 110 μm;
[0057] The particle size of the baddeleyite is 120 μm;
[0058] The particle size of the magnesite is 60 μm;
[0059] The particle size of the zinc oxide is 40 nm;
[0060] The preparation method of the daily-use ceramic comprises the following steps:
[0061] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a speed of 300 rpm for 20 h;
[0062] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 500-mesh sieve; the vacuum drying temperature is 80° C., and the drying time is 12 h;
[0063] (3) The sieved powder was calcined at 700°C in a muffle furnace under a nitrogen atmosphere for 4 h, and then calcined at 900°C for 2 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed evenly with sodium polyacrylate, and a green body was formed according to the shape by dry pressing, and the dry pressing pressure was 80 MPa; then the green body was hot pressed and sintered at a heating rate of 4°C / min, and the temperature was raised to 700°C, and the temperature was kept for 3 h, and then the temperature was raised to 1350°C at a heating rate of 12°C / min, and the sintering pressure was 60 MPa, and the sintering was performed for 1 h, and then naturally cooled to room temperature to obtain the product.
[0064] Example 3
[0065] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0066] 40 parts of porcelain stone; 20 parts of talc; 15 parts of diopside; 10 parts of baddeleyite; 1 part of magnesite; 8 parts of MOF material; 2 parts of zinc oxide, 8 parts of sodium polyacrylate; 30 parts of water;
[0067] The preparation method of the MOF material comprises the following steps:
[0068] 0.02 mol of indium chloride, 0.03 mol of copper nitrate, 1 mol of nickel acetate and 3 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 120-160° C. for 10-20 h, filtered, washed, and dried at 80-120° C. for 10-14 h to obtain a MOF material.
[0069] The particle size of the porcelain stone is 80 μm;
[0070] The particle size of the talc is 140 μm;
[0071] The particle size of the diopside is 70 μm;
[0072] The particle size of the baddeleyite is 160 μm;
[0073] The particle size of the magnesite is 20 μm;
[0074] The particle size of the zinc oxide is 80 nm;
[0075] The preparation method of the daily-use ceramic comprises the following steps:
[0076] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a ball milling speed of 100 rpm for 40 h;
[0077] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 300-mesh sieve; the vacuum drying temperature is 60° C. and the drying time is 16 h;
[0078] (3) The sieved powder was calcined at 500°C in a muffle furnace under a nitrogen atmosphere for 6 h, and then calcined at 800°C in an air atmosphere for 4 h. After calcination, the powder was ground to obtain a powder, and then the obtained powder was evenly mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing, and the dry pressing pressure was 40 MPa; then the formed green body was hot-pressed and sintered at a heating rate of 2°C / min to 500°C, kept at this temperature for 5 h, and then heated to 1250°C at a heating rate of 8°C / min, sintered at a sintering pressure of 40 MPa, sintered for 3 h, and then naturally cooled to room temperature to obtain the product.
[0079] Comparative Example 1
[0080] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0081] 50 parts of porcelain stone; 15 parts of talc; 28 parts of diopside; 2 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0082] The preparation method of the MOF material comprises the following steps:
[0083] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0084] The particle size of the porcelain stone is 120 μm;
[0085] The particle size of the talc is 100 μm;
[0086] The particle size of the diopside is 90 μm;
[0087] The particle size of the magnesite is 40 μm;
[0088] The particle size of the zinc oxide is 60 nm;
[0089] The preparation method of the daily-use ceramic comprises the following steps:
[0090] (1) Porcelain stone, talc, diopside, magnesite, MOF material, zinc oxide and water are placed in a ball mill and ball milled at a speed of 200 rpm for 30 h;
[0091] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0092] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0093] Comparative Example 2
[0094] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0095] 50 parts of porcelain stone; 15 parts of talc; 28 parts of baddeleyite; 2 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0096] The preparation method of the MOF material comprises the following steps:
[0097] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0098] The particle size of the porcelain stone is 120 μm;
[0099] The particle size of the talc is 100 μm;
[0100] The particle size of the baddeleyite is 140 μm;
[0101] The particle size of the magnesite is 40 μm;
[0102] The particle size of the zinc oxide is 60 nm;
[0103] The preparation method of the daily-use ceramic comprises the following steps:
[0104] (1) Porcelain stone, talc, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0105] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0106] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0107] Comparative Example 3
[0108] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0109] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 10 parts of baddeleyite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0110] The preparation method of the MOF material comprises the following steps:
[0111] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0112] The particle size of the porcelain stone is 120 μm;
[0113] The particle size of the talc is 100 μm;
[0114] The particle size of the diopside is 90 μm;
[0115] The particle size of the baddeleyite is 140 μm;
[0116] The particle size of the zinc oxide is 60 nm;
[0117] The preparation method of the daily-use ceramic comprises the following steps:
[0118] (1) Porcelain stone, talc, diopside, baddeleyite, MOF material, zinc oxide and water were placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0119] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0120] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0121] Comparative Example 4
[0122] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0123] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 10 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0124] The preparation method of the MOF material comprises the following steps:
[0125] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0126] The particle size of the porcelain stone is 120 μm;
[0127] The particle size of the talc is 100 μm;
[0128] The particle size of the diopside is 90 μm;
[0129] The particle size of the magnesite is 40 μm;
[0130] The particle size of the zinc oxide is 60 nm;
[0131] The preparation method of the daily-use ceramic comprises the following steps:
[0132] (1) Porcelain stone, talc, diopside, magnesite, MOF material, zinc oxide and water are placed in a ball mill and ball milled at a speed of 200 rpm for 30 h;
[0133] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0134] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0135] Comparative Example 5
[0136] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0137] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 8 parts of baddeleyite; 2 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0138] The preparation method of the MOF material comprises the following steps:
[0139] 0.05 mol of indium nitrate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0140] The particle size of the porcelain stone is 120 μm;
[0141] The particle size of the talc is 100 μm;
[0142] The particle size of the diopside is 90 μm;
[0143] The particle size of the baddeleyite is 140 μm;
[0144] The particle size of the magnesite is 40 μm;
[0145] The particle size of the zinc oxide is 60 nm;
[0146] The preparation method of the daily-use ceramic comprises the following steps:
[0147] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0148] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0149] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0150] Comparative Example 6
[0151] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0152] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 8 parts of baddeleyite; 2 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0153] The preparation method of the MOF material comprises the following steps:
[0154] 0.05 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0155] The particle size of the porcelain stone is 120 μm;
[0156] The particle size of the talc is 100 μm;
[0157] The particle size of the diopside is 90 μm;
[0158] The particle size of the baddeleyite is 140 μm;
[0159] The particle size of the magnesite is 40 μm;
[0160] The particle size of the zinc oxide is 60 nm;
[0161] The preparation method of the daily-use ceramic comprises the following steps:
[0162] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0163] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0164] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0165] Comparative Example 7
[0166] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0167] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 8 parts of baddeleyite; 2 parts of magnesite; 10 parts of MOF material; 6 parts of sodium polyacrylate; 35 parts of water;
[0168] The preparation method of the MOF material comprises the following steps:
[0169] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0170] The particle size of the porcelain stone is 120 μm;
[0171] The particle size of the talc is 100 μm;
[0172] The particle size of the diopside is 90 μm;
[0173] The particle size of the baddeleyite is 140 μm;
[0174] The particle size of the magnesite is 40 μm;
[0175] The preparation method of the daily-use ceramic comprises the following steps:
[0176] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material and water were placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0177] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0178] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0179] Comparative Example 8
[0180] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0181] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 8 parts of baddeleyite; 2 parts of magnesite; 10 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0182] The particle size of the porcelain stone is 120 μm;
[0183] The particle size of the talc is 100 μm;
[0184] The particle size of the diopside is 90 μm;
[0185] The particle size of the baddeleyite is 140 μm;
[0186] The particle size of the magnesite is 40 μm;
[0187] The particle size of the zinc oxide is 60 nm;
[0188] The preparation method of the daily-use ceramic comprises the following steps:
[0189] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, zinc oxide and water are placed in a ball mill and ball milled at a speed of 200 rpm for 30 h;
[0190] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0191] (3) The sieved powder was calcined at 600°C in a muffle furnace under a nitrogen atmosphere for 5 h, and then calcined at 850°C for 3 h in an air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing. The dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min to 600°C, kept at this temperature for 4 h, and then sintered at a heating rate of 10°C / min to 1300°C, a sintering pressure of 50 MPa, sintered for 2 h, and then naturally cooled to room temperature to obtain the product.
[0192] Comparative Example 9
[0193] A daily-use ceramic, comprising the following raw materials in parts by weight:
[0194] 50 parts of porcelain stone; 15 parts of talc; 20 parts of diopside; 8 parts of baddeleyite; 2 parts of magnesite; 6 parts of MOF material; 4 parts of zinc oxide, 6 parts of sodium polyacrylate; 35 parts of water;
[0195] The preparation method of the MOF material comprises the following steps:
[0196] 0.03 mol of indium nitrate, 0.02 mol of copper acetate, 1 mol of nickel chloride and 4 mol of 2-methylimidazole were dissolved in 200 mL of ethanol-water (the volume ratio of ethanol to water was 1:1) to obtain a mixed solution, which was then hydrothermally reacted at 140°C for 16 hours, filtered, washed, and dried at 100°C for 12 hours to obtain a MOF material.
[0197] The particle size of the porcelain stone is 120 μm;
[0198] The particle size of the talc is 100 μm;
[0199] The particle size of the diopside is 90 μm;
[0200] The particle size of the baddeleyite is 140 μm;
[0201] The particle size of the magnesite is 40 μm;
[0202] The particle size of the zinc oxide is 60 nm;
[0203] The preparation method of the daily-use ceramic comprises the following steps:
[0204] (1) Porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water are placed in a ball mill for ball milling at a speed of 200 rpm for 30 h;
[0205] (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 400-mesh sieve; the vacuum drying temperature is 70° C. and the drying time is 14 h;
[0206] (3) The sieved powder was calcined at 600°C in a muffle furnace under air atmosphere for 5 h, and then calcined at 850°C for 3 h under air atmosphere. After calcination, the powder was ground to obtain a powder, and then the obtained powder was mixed with sodium polyacrylate, and a green body was formed according to the shape by dry pressing method, and the dry pressing pressure was 60 MPa; then the green body was hot pressed and sintered at a heating rate of 3°C / min, and the temperature was raised to 600°C, and the temperature was kept for 4 h, and then the temperature was raised to 1300°C at a heating rate of 10°C / min, and the sintering pressure was 50 MPa, and the sintering was carried out for 2 h, and then naturally cooled to room temperature to obtain the product.
[0207] The mechanical properties of the daily-use ceramics of Examples 1-3 and Comparative Examples 1-4 were tested. The specific test results are shown in Table 1:
[0208] The specific test methods are as follows:
[0209] The flexural strength of the samples was tested using a PT-1036PC universal material testing machine. The sample size was 4 mm × 5 mm × 30 mm, the span was 16 mm, the indenter loading speed was 0.4 mm / min, and the flexural strength was the average of three measurement results.
[0210] Table 1.
[0211] Flexural strength(MPa) Flexural strength(MPa) Example 1 389.5 Comparative Example 2 357.8 Example 1 381.3 Comparative Example 3 348.4 Example 1 384.7 Comparative Example 4 323.6 Comparative Example 1 338.4
[0212] It can be seen from Table 1 that the present invention significantly improves the mechanical properties of daily-use ceramics by utilizing the interaction between diopside, baddeleyite and magnesite.
[0213] The antibacterial properties of the daily-use ceramics of Examples 1-3 and Comparative Examples 5-9 were tested. The specific test results are shown in Table 2:
[0214] The samples of Examples 1-3 and Comparative Examples 5-9 were placed in culture dishes of Escherichia coli, Staphylococcus aureus, and Candida albicans, respectively, and the antibacterial rates were tested at 10 hours under sunlight. Each strain was cultured at 25°C for 14 hours:
[0215] Table 2:
[0216]
[0217] It can be seen from Table 2 that the daily-use ceramics prepared by the present application using specific raw materials and methods have excellent antibacterial properties and can achieve long-term antibacterial properties, and have excellent application prospects.
[0218] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A daily-use ceramic, characterized in that: The daily-use ceramics include the following raw materials by weight: 40-60 parts of porcelain stone; 10-20 parts of talc; 15-25 parts of diopside; 6-10 parts of baddeleyite; 1-3 parts of magnesite; 4-8 parts of MOF material; 2-6 parts of zinc oxide, 4-8 parts of sodium polyacrylate; 30-40 parts of water; The preparation method of the MOF material comprises the following steps: Indium salt, copper salt, nickel salt and 2-methylimidazole are dissolved in an ethanol aqueous solution to obtain a mixed solution, and then hydrothermally react at 120-160° C. for 10-20 hours, filter, wash, and dry at 80-120° C. for 10-14 hours to obtain a MOF material; the molar ratio of the indium salt, copper salt, nickel salt and 2-methylimidazole is: 0.02-0.04:0.01-0.03:1:3-5; The preparation method of the daily-use ceramic comprises the following steps: (1) Put porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water in a ball mill for ball milling; (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 300-500 mesh sieve; (3) calcining the sieved powder in a muffle furnace at 500-700° C. for 4-6 hours under a nitrogen atmosphere, and then calcining at 800-900° C. for 2-4 hours under an air atmosphere, grinding the powder after calcination, and then mixing the powder with sodium polyacrylate, forming a green body according to the shape by dry pressing, and the dry pressing pressure is 40-80 MPa; then hot pressing the green body, and then naturally cooling it to room temperature to obtain; The specific steps of the hot pressing sintering are: heating up to 500-700°C at a heating rate of 2-4°C / min, keeping the temperature for 3-5h, then heating up to 1250-1350°C at a heating rate of 8-12°C / min, sintering at a sintering pressure of 40-60MPa, and sintering for 1-3h.
2. A daily-use ceramic according to claim 1, characterized in that: The indium salt is at least one of indium nitrate, indium acetate, and indium chloride; the copper salt is at least one of copper nitrate, copper acetate, and copper chloride; and the nickel salt is at least one of nickel nitrate, nickel acetate, and nickel chloride.
3. A daily-use ceramic according to claim 1, characterized in that: The particle size of the porcelain stone is 80-160 μm; the particle size of the talc is 60-140 μm; and the particle size of the diopside is 70-110 μm.
4. A daily-use ceramic according to claim 1, characterized in that: The particle size of the baddeleyite is 120-160 μm; the particle size of the magnesite is 20-60 μm; and the particle size of the zinc oxide is 40-80 nm.
5. A method for preparing daily-use ceramics according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) Put porcelain stone, talc, diopside, baddeleyite, magnesite, MOF material, zinc oxide and water in a ball mill for ball milling; (2) After the ball milling is completed, the obtained mixed material is vacuum dried, and then ground. The ground powder is passed through a 300-500 mesh sieve; (3) calcining the sieved powder in a muffle furnace at 500-700° C. for 4-6 hours under a nitrogen atmosphere, and then calcining at 800-900° C. for 2-4 hours under an air atmosphere, grinding the powder after calcination, and then mixing the powder with sodium polyacrylate, forming a green body according to the shape by dry pressing, and the dry pressing pressure is 40-80 MPa; then hot pressing the green body, and then naturally cooling it to room temperature to obtain; The specific steps of the hot pressing sintering are: heating up to 500-700°C at a heating rate of 2-4°C / min, keeping the temperature for 3-5h, then heating up to 1250-1350°C at a heating rate of 8-12°C / min, sintering at a sintering pressure of 40-60MPa, and sintering for 1-3h.
6. The method for preparing daily-use ceramics according to claim 5, characterized in that: In step (1), the ball milling speed is 100 to 300 rpm, and the ball milling time is 20 to 40 hours.
7. The method for preparing daily-use ceramics according to claim 5, characterized in that: In step (2), the vacuum drying temperature is 60 to 80° C., and the drying time is 12 to 16 hours.
8. Application of the daily-use ceramic according to any one of claims 1 to 4 in the antibacterial field.
Citation Information
Patent Citations
A high-performance antibacterial daily ceramic and its preparation method
CN113149678B
Color-changing glaze ceramic and production method thereof
CN103693992A
Low-temperature & quick-burning sanitary china with diopside as flux
CN1069013A